Geoinformation modeling for wind erosion - Moskalenko, A.; Heryn, A. (Land Management, Cadastre and Land Monitoring, 2023)
Possibilities of application of geoinformation modeling for areas that may be affected by erosion are considered. An analysis of the state of studying the issue of modeling erosion processes and automation of decision-making support was carried out.This study describes the structuring of a general algorithm for determining areas that may be affected by wind erosion through a functional model. The article provides an analysis of the factors affecting the soil's resistance to erosion. A geo-information model for constructing a geo-image of erosion-hazardous lands has been developed and implemented.As a result of the work carried out, it was determined that an algorithm can be used to determine areas that may be affected by wind erosion, which allows automating some stages of determining areas that may be affected by wind erosion.The results of the work can be used in the formation of spatial decisions regarding the rational use and protection of land.
Keywords: geoinformation modeling; model; wind erosion; geoimagery